PENGARUH PENDAPATAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA KELAS XI SMAN 2 PEKANBARU - Pingkan Septhalia; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of family income on the motivation of students learning class XI SMA Negeri 2 Pekanbaru. Population in the study of students class XI amounted to 312 people and the sample obtained by using proportional random sampling technique as much as 76 respondents. Data analysis techniques used are descriptive quantitative analysis, simple linear regression analysis. The result of this study is family income significant influence the student learning motivation. Simple linear regression equation obtained in this study is Y = 72,980 + 3,502X. Coefficient of determination (R2) equal to 37,6%.Key Words: Family Income, Learning Motivation